Designing Vertical Type Mangosteen Leather Penepung Machine - Ahmad Junaidin; Sirajuddin Haji Abdullah; Rosyid Ridho (Universitas Muhammadiyah Mataram, 2021)
The mangosteen fruit (Garcinia mangostana L.) or nicknamed the queen of fruit is one of Indonesia's leading fruits. The mangosteen fruit consists of components in the form of seeds, fruit, pulp (pulp), and fruit skin. This mangosteen rind flouring device is a tool to assist in the flouring process in large quantities using an electric motor as a driving force. The method used in this research is an experimental method by conducting experiments directly in the field and in the laboratory. The design used was a completely randomized design (CRD) which consisted of 3 treatments using variations in the stages of material entry (load), namely: P1 = Load 100 g with a rotation of 1430 rpm, P2 = Load 200 g (100 g + 100 g) with a rotation 1430 rpm, P3 = Load 300 g (150 g +150 g ) with a rotation of 1430 rpm. The data analysis used in this research is a mathematical approach using Microsoft Excel and a statistical approach using ANOVA diversity analysis and a 5% BNJ follow-up test. This study uses 3 parameters, namely, capacity (kg/hour), power requirements (watts), and engine efficiency (%) with results that have no significant effect. The results of the design of the mangosteen rind flouring device of vertical type with dimensions of 58 cm long, 43 cm wide and 63 cm high. The effective working capacity of this mangosteen rind powder is found at P3 of 342.92 g/second with an output rotation of 1430 r pm which is used in testing the tool. The effective electric motor power is at P1 the average motor power usage is 7.08 watts. The percentage of engine efficiency in this study is found in P1 of 63.83%.